(untitled) (GYMNASIUM, 2008)
The incapacity of the school to form permanent motion skills has urged us to search for new, durable solutions, to submit another manner for the application of the methods pertaining to physical education and sport. Psycho-body motion counsel is based on the generalization of the psycho-body motion data to the purpose of the individual choice and application, upon the case, of the physical education methods, by the psycho-body motion counselor, to the purpose of fitting within a system of continous education aiming at the harmonious and performantial physical development.